Drivers of Collembola assemblages along an altitudinal gradient in northeast China. Issue 2 (12th February 2022) - Xie, Zhijing; Sun, Xin; Lux, Johannes; Chen, Ting‐Wen; Potapov, Mikhail; Wu, Donghui; Scheu, Stefan
Abstract: Altitudinal changes in the diversity of plants and animals have been well documented; however, soil animals received little attention in this context and it is unclear whether their diversity follows general altitudinal distribution patterns. Changbai Mountain is one of few well‐conserved mountain regions comprising natural ecosystems on the Eurasian continent. Here, we present a comprehensive analysis of the diversity and community composition of Collembola along ten altitudinal sites representing five vegetation types from forest to alpine tundra. Among 7834 Collembola individuals, 84 morphospecies were identified. Species richness varied marginally significant with altitude and generally followed a unimodal relationship with altitude. By contrast, the density of Collembola did not change in a consistent way with altitude. Collembola communities changed gradually with altitude, with local habitat‐related factors (soil and litter carbon‐to‐nitrogen ratio, litter carbon content, and soil pH) and climatic variables (precipitation seasonality) identified as major drivers of changes in Collembola community composition. Notably, local habitat‐related factors explained more variation in Collembola assemblages than climatic variables. The results suggest that local habitat‐related factors including precipitation and temperature are the main drivers of changes in Collembola communities with altitude. Specifically, soil and litter carbon‐to‐nitrogen ratio correlated positively with Collembola communities at high altitudes, whereas soil pH correlated positively at low altitudes. This documents that altitudinal gradients provide unique opportunities for identifying factors driving the community composition of not only above‐ but also belowground invertebrates. Abstract : The results suggest that local habitat‐related factors including precipitation and temperature are the main drivers of changes in Collembola communities with altitude. Specifically, soil and litter carbon‐to‐nitrogen ratio correlated positively with Collembola communities at high altitudes, whereas soil pH correlated positively at low altitudes. This documents that altitudinal gradients provide unique opportunities for identifying factors driving the community composition of not only above‐ but also belowground invertebrates.